HUBUNGAN ANTARA KECEPATAN LARI DENGAN KEMAMPUAN MENGGIRING BOLA SEPAK PADA SISWA USIA 13-14 TAHUN SSB UNIBRAW 82 MALANG - Doni Kurniawan; Siti Nurrochmah; Febrita Pauilina Heynoek (Fakultas Ilmu Keolahragaan UM)
Abstract:Dribbling a soccer ball is to carry the ball with the leg with a goal past opponents to seek opportunities gave feedback to colleagues and to hold the ball stays on the tenure and easier to outwit your opponent and pass through an opponent. Dribbling a soccer ball requires good skills and the support of elements of good physical condition such as speed can provide faster movement capabilities. Aspects of running speed is very necessary in the game of football, because the escape velocity is high then a player who dribbles a soccer can break and weaken the defense area of the opponent, so that aspect of running speed in the game of football is very important to be trained from students early age and improved through methods for correct and regular practice.Keywords: Soccer, Dribbling, Sprint, Students ages 13-14.